2007
DOI: 10.1080/14015430600630860
|View full text |Cite
|
Sign up to set email alerts
|

Prosodic contextualization of minimal responses to yes/no-questions in aphasic talk-in-interaction: A descriptive single-case study of a Norwegian aphasic speaker

Abstract: The article explores aspects of the role of prosody as a contextualisation cue in aphasic conversation through auditory and acoustic analysis of an aphasic speaker's use of pitch variation in responses to closed yes/no-requests. The results reveal two prosodic realisations of 'yes' and 'no' contextualising different kinds of responses: a flat realisation with no prolongation and minimal pauses, signalling decisiveness, and a realisation with movement in pitch, prolongation and preceding pauses, signalling inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
1
6
1
Order By: Relevance
“…Contrary to the claim emerging from the experimental literature (Niemi, 1998;Shapiro & Danly, 1985) which assumes that the temporal level is more severely impaired compared to the fundamental frequency level, we found that both temporal and fundamental frequency cues can be employed successfully to accomplish differentiation of interactional uses. The claim has also been made that longer utterances show more temporal disturbance as a result of shorter speech planning units Adaptation to aphasia 67 (Lind, 2007;Seddoh, 2002Seddoh, , 2004. However, our results cannot support or contest this since we did not include full utterances and their length into our prosodic analysis.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Contrary to the claim emerging from the experimental literature (Niemi, 1998;Shapiro & Danly, 1985) which assumes that the temporal level is more severely impaired compared to the fundamental frequency level, we found that both temporal and fundamental frequency cues can be employed successfully to accomplish differentiation of interactional uses. The claim has also been made that longer utterances show more temporal disturbance as a result of shorter speech planning units Adaptation to aphasia 67 (Lind, 2007;Seddoh, 2002Seddoh, , 2004. However, our results cannot support or contest this since we did not include full utterances and their length into our prosodic analysis.…”
Section: Discussioncontrasting
confidence: 73%
“…These aphasic speakers were able to indicate continuation or non-terminal lexical items with level pitch or minor pitch rise and turn-terminal items with pitch falls and rises in order. Lind (2007) showed in an auditory and acoustic analysis of conversations with a native speaker of Norwegian that pitch variation in minimal response words in the sequential context following closed yes/no-questions can be utilized as a contextualization cue by the non-fluent patient. Participant orientation evidence indicated that decisive and indecisive responses are differently realized prosodically.…”
Section: Aphasia and Prosodymentioning
confidence: 99%
“…By combining the limited verbal output, ranging from a few words to lexically empty syllables, with variations in pitch and volume, non-fluent PWA have been shown to convey meaning. Examples are signalling a demand for attention, calling an addressee, expressing uncertainty, agreement, enthusiasm or appreciation, managing interaction and turn-taking and finally requesting for something to happen such as for someone to continue or stop guessing, or for the provision of information (Goodwin, 1995(Goodwin, , 2000Oelschlaeger & Damico, 1998;Lind, 2007;Rhys et al, 2013;Beeke et al, 2007Beeke et al, , 2009. Dogil et al (1990) presented a case study of a PWA with fluent aphasia who compensated for his language impairment by effectively using unimpaired prosodic skills.…”
Section: Prosodymentioning
confidence: 99%
“…In line 18 the prolonged 'no' is followed by a pause and then the series of accounts in mention. Neither of the tokens are, then, followed by signs of indecisiveness (as prolonged no in response to yes/no questions has also been documented to signal, see Lind 2007). Prolongation of words and sounds may construe a response as dispreferred, that is, socially problematic (Schegloff 1988).…”
Section: Case Study 1: Accepting the Patient's Requestmentioning
confidence: 99%